Numerical Modeling of the Complex Link Between Grain Refinement and Microsegregation in Binary Alloy Solidification - Daneshifar, M. H.; Jabbareh, M. A. (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2022)
Microsegregation is an important phenomenon occurring during solidification, with potentially detrimental effects such as formation of brittle intermetallics at the later stages of solidification, hence leading to degraded mechanical properties and workability of cast products. Grain refinement is a well-established treatment in casting plants to achieve cast structures with fine equiaxed grains and enhance chemical homogeneity. Although both subjects have been deeply studied over the past decades, there are few reports dealing with the link between grain refinement and microsegregation. The present work aims to address this problem through spatially resolved simulation of microstructure evolution during solidification of a model binary system. The simulations show how increasing the number density of inoculant particles results not only in the reduction of the average grain size, but also in a change of morphology from dendritic to globular. The combination of these two effects results in a complex trend, manifested by a non-monotonic correlation between the level of microsegregation and the number density of the inoculants. This means that, in contrast to the predictions of the commonly used Scheil model, there can be a specific number density of seeds for which microsegregation is at the highest level. The simulation results are shown to be consistent with the experiments on Al-2.1 at. pct Cu alloy and discussed in view of the relevant physical factors and industrial implications.